Causes and Presentation Of Cervical Lymphadenopathy - Arifullah Bangash; Syed Zafar Hassan; Ghulam Muhammad (Gandhara University, 2018)
OBJECTIVE To determine the proportion of cervical lymphadenopathy in systemic diseases, their presentation and investigative tools. METHODOLOGY This descriptive study was carried out from 1st July 2014 to 30 June 2017 in ENT and head and neck department Naseer Teaching Hospital and Town Teaching Hospital, Peshawar. Total of 270 patients with enlarged cervical lymph nodes, of either sex and of any age were approached for inclusion into the study. Patients with suspected acute inflammation were given a trial of antibiotic and followed for two weeks were excluded from the study. Excisional biopsy of the lymph nodes was performed in all these patients with six weeks or more duration. RESULTS In our study out of 270 patients, 158 (58.5%) were males and the majority of patients (63.3%) had ages from 11-40 years. Tuberculous cervical lymphadenopathy was diagnosed in 145 (53.7%) patients, reactive hyperplasia in 53 (19.6%), lymphoma in 32 (11.8 %,) metastasis to cervical lymph nodes in 30 (11.1%), sarcoidosis in 7 (2.6%) and other very rare conditions as Kawasaki, Kikuchie and Rosi Dorfman were found in only one of each (0.4%). About 136 (50.4%) of the patients had involvement of multiple lymph nodes while 134 (49.6%) had single swelling. The matted lymph nodes were found in 162 (60%) whereas discrete lymph nodes were found in only 108 (40%) cases. Cold abscess was found in 19 (7%) of patients. CONCLUSION Tuberculosis is the commonest cause of cervical lymphadenopathy, with the majority of these patients having multiple lymph node involvement. In children, usually cervical lymphadenopathy is reactive or infective while in older age mostly metastatic.